2017
DOI: 10.1097/md.0000000000006877
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary interventions and continuous quality improvement to reduce unplanned extubation in adult intensive care units

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
(23 reference statements)
0
30
0
2
Order By: Relevance
“…This practice promotes a culture of safety. Multiple studies have shown QI methodologies can successfully decrease not only UE, but improved patient transfers, reduce lengths of mechanical ventilation and overall improve patient safety, 2830 and that direct observation and overall promotion of a safety culture can drive change. 31,32 This leads to systems that are highly reliably and promote quality of care, and as shown by Lyren et al 33 effectively reduce hospital-acquired harm.…”
Section: Discussionmentioning
confidence: 99%
“…This practice promotes a culture of safety. Multiple studies have shown QI methodologies can successfully decrease not only UE, but improved patient transfers, reduce lengths of mechanical ventilation and overall improve patient safety, 2830 and that direct observation and overall promotion of a safety culture can drive change. 31,32 This leads to systems that are highly reliably and promote quality of care, and as shown by Lyren et al 33 effectively reduce hospital-acquired harm.…”
Section: Discussionmentioning
confidence: 99%
“…The reintubation rate in patients with UE ranges from 1.8% to 88%, and these patients are at a higher risk of difficult intubation and hypoxemia. [ 1 , 3 , 5 , 6 ] Mort [ 7 ] performed a study on 61 patients who had reintubation within 3 days after UE. In total, 54 (89%) patients required reintubation within 2 hours, and 40 (66%) patients were reintubated within 30 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Within the PI category, studies were conducted most frequently in the United States ( n = 25) ( 34 59 ) followed by Canada ( n = 3) ( 60 62 ), Spain ( n = 3) ( 63 65 ), Germany ( n = 2) ( 66 , 67 ), Norway ( n = 2) ( 68 , 69 ), and one study each from South Africa ( 70 ), Argentina ( 71 ), China ( 72 ), France ( 73 ), The Netherlands ( 74 ), Saudi Arabia ( 75 ), and the United Kingdom ( 56 ). Studies that reported using a QI design were conducted in the United States ( n = 11) ( 76 86 ), Australia ( n = 2) ( 87 , 88 ), and one each in Brazil ( 89 ), Canada ( 90 ), China ( 91 ), Sweden ( 92 ), Taiwan ( 93 ), and the United Kingdom ( 94 ). Many studies (30/82, 36.5%) included more than one critical care unit in their investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The studies addressed a variety of EBPs, classified into 18 categories. The most common EBPs included: ventilator-associated pneumonia (VAP) prevention bundles (12/82, 14.6%) ( 14 , 33 , 39 , 49 , 54 , 55 , 57 , 59 , 60 , 63 , 73 , 86 ), nutritional support/management protocols (9/82, 10.9%) ( 25 , 26 , 30 , 35 , 38 , 40 , 61 , 88 , 90 ), the Awakening and Breathing Coordination, Delirium Monitoring/Management, and Early Exercise/Mobility (ABCDE/ABCDEF) bundle (7/82, 8.5%) ( 15 19 , 47 , 76 ), central line-associated bloodstream infection (CLABSI) prevention bundles (6/82, 7.3%) ( 22 , 37 , 42 , 52 , 53 , 80 ), and mechanical ventilation liberation/weaning protocols (6/82, 7.3%) ( 36 , 62 , 69 , 72 , 90 , 93 ). Sixteen studies involved ICU mobilization protocols (4/82, 4.8%) ( 34 , 46 , 70 , 78 ), use of checklists (4/82, 4.8%) ( 41 , 81 , 84 , 89 ), hand hygiene/infection control bundles ( n = 4/82, 4.8%) ( 21 , 66 , 71 , 95 ), and initiatives targeting multiple EBPs (4/82, 4.8%) ( 24 , 51 , 56 , 77 ).…”
Section: Resultsmentioning
confidence: 99%